Postmodern, Marxist, and Christian historical novels - Hinojosa, Lynne W., 1966- author.
1 online resource.
Keywords: "Postmodern, Marxist, and Christian Historical Novels: Hope and the Burdens of History argues historical novels can help readers receive the burdens of history--meaning both the burdens of the past, present, and future and the burden of living in time--and develop a more robust conception of and concrete practice of hope. Since the 1960s, historical novels have been a dominant literary genre, but they have been influenced primarily not by Christian but by postmodern and marxist thinkers and writers. This book provides a theological and literary analysis of all three types of historical novels--postmodern, marxist, and Christian--and outlines what each school of thought can learn from each other regarding historical understanding and hope. Using Jürgen Moltmann's theology of hope and Frank Kermode's literary criticism as a theoretical basis, the book offers readings of novels by Julian Barnes, A.S. Byatt, Kazuo Ishiguro, Margaret Atwood, Michael Ondaatje, Ian McEwan, and Ursula LeGuin, among others, and ends with an extended analysis of Marilynne Robinson's Gilead series"--